Implementing a Civic Skills-Focused Problem Posing Model to Enhance Problem-Solving Competencies in Elementary School Students: A Systematic Literature Review - Najwa Syarofa; Rusmansyah Rusmansyah; Isnawati Isnawati (Pascasarjana UM, 2022)
This systematic literature review explores the application of the Problem Posing Model, a holistic educational approach, in civic education to enhance elementary school students' problem-solving abilities. By fostering a comprehensive understanding of conflict resolution and cooperative problem solving, civic skills, derived from civic knowledge, become meaningful tools in addressing national and societal issues. This review methodology involves the identification, review, evaluation, and interpretation of empirical studies conducted over the past five years (2018-2022), focused on applying a civic skills-oriented problem-posing model in elementary education. The initial search yielded approximately 250 articles from databases such as ERIC, Google Scholar, and Sinta. After a meticulous process, 20 articles, primarily from high schools and universities, were chosen for the review using three primary keywords: problem-posing models, civic skills, and problem-solving abilities. The selected articles were published in international or national educational journals, including Scopus and Sinta, adhering to specific criteria such as the focus on Civics learning strategies, addressing misconceptions about the application of problem-posing models and problem-solving, and publication within the last five years in Scopus (Q1-Q4) and Sinta (S1-S4) indexed journals. The research findings indicate that the problem-posing model enhances students' critical thinking and creativity, proving more effective than conventional teaching methods. The integration of civic skills in Civics subjects boosts students' active participation, fostering attitudes of tolerance, cooperation, and responsibility. Therefore, the application of a civic skills-oriented problem-posing model can significantly improve students' ability to analyze problems critically, demonstrating openness, tolerance, and accountability.